THE MODERN TENDENCIES AND PROSPECTS OF THE DEVELOPMENT OF LOCAL SELF-GOVERMENT IN POLAND: ESTIMATION OF EXPERTS (PART 2) - Бровко, О. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The article reviewed the current state of local self-government in Poland after 25 years ofgmina reform. The level of autonomy and independence of local self-government in Poland wasanalysed. It was established how and in what measure funding of administrative - territorial units oflocal government in Poland is done. The main forms of public participation in the local level inPoland were determined. The answer to the question, if the local self-government needs the furtherchanges in Poland was given. The study was carried out through in-depth interviews with leadingPolish experts in local self-government.